Terahertz transitions in narrow-gap carbon nanotubes and graphene nanoribbons - Saroka, V. A. (Animo Repository, 2018)
© The Authors, published by EDP Sciences. We show that the curvature effects in quasi-metallic carbon nanotubes and edge effects in narrow-gap graphene nanoribbons not only open band gaps in the THz range but also result in giant enhancement of the transition probabilities across these gaps. This makes these nanostructures perspective candidates for sources and detectors of THz radiation.